Eludicating The Human Immune Response To Hookworm Infecions: Literature Review - Shafira, Ellyta; Firmansyah, Yohanes (Universitas Pahlawan Tuanku Tambusai, 2024)
Parasitic infections, particularly those caused by hookworms, pose a significant challenge to global health, affecting millions in developing regions. Understanding the human immune response to such infections is crucial for developing effective interventions. This review provides a comprehensive overview of the innate and adaptive immune responses mobilized against hookworms, emphasizing the roles of various immune cells and the interplay between different immune mechanisms. A systematic literature review was conducted, focusing on studies published from January 2010 to the present. Databases such as PubMed, Scopus, Web of Science, and Google Scholar were searched using terms related to parasitic infections, immune responses, and hookworm pathology. Both experimental and review articles were included to extract detailed information on cellular and molecular immune responses to parasitic infections. The review highlights the dual role of innate and adaptive immunity in combating hookworm infections. Innate immunity acts as the first line of defense through mechanisms like inflammation and the production of antimicrobial peptides. Adaptive immunity provides a more targeted response, involving T and B cells and the production of specific antibodies. The interaction between these immune components and the modulation of immune responses, including the Th1/Th2 balance, are critical for the host's defense and the pathogenesis of hookworm infections. The intricate immune responses to hookworm infections underscore the complexity of host-parasite interactions. Understanding these responses is essential for developing novel therapeutic and preventive strategies against hookworm and other parasitic infections. Future research should focus on unraveling the detailed mechanisms of immunity and exploring the potential for vaccine development and immune-based therapies.